Fecal Microbiota Transplantation: A Potential Tool for Treatment of Human Female Reproductive Tract Diseases - Quaranta, Gianluca; Sanguinetti, Maurizio; Masucci, Luca (Frontiers in Immunology, 2019)
ABSTRACT. The gastro-intestinal tract is an extensive organ involved in several activities, with a crucial role in immunity. Billions of commensal and transient microorganisms, known as the gut microbiota, and potential pathogens, which are constantly stimulating intestinal immunity, colonize the intestinal epithelial surface. The gut microbiota may be regarded as analogous to a solid organ with multiple different functions. In the last decade, many studies have demonstrated that intestinal bacteria can be a decisive factor in the health-disease balance of the intestine, and they can also be responsible for illnesses in other locations. For this reason, faecal microbiota transplantation (FMT) represents an important therapeutic option for Clostridium difﬁcile infections and hold promise for different clinical conditions, such as multiple sclerosis, autism, obesity and other systemic diseases. FMT consists of the infusion of a faecal suspension from a healthy donor to a recipient in order to restore gut flora alterations. Similar to the gut, the female reproductive tract is an example of a very complex biological ecosystem. Recent studies indicate a possible relationship between the gut and female tract microbiota, associating specific intestinal bacteria patterns with genital female diseases, such as polycystic ovary syndrome (PCOS), endometriosis and bacterial vaginosis (BV). FMT could represent a potential innovative treatment option in this field.